Competitiveness of products as a basic element in the implementation of strategic goals of enterprise - Солоха, Д. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The questions of providing of competitive edges of products are considered, her descriptions are certain as a base of realization of aims of enterprise in a long-term strategic prospect.